Relação entre cultura e gargalos na gestão de processos em uma Administração Pública - Luz, Jéssica Maria da (2023)
This study's main objective is to identify the challenges of process management in a Municipal Public Administration, and to present ways for the implementation of this system to be efficient and bring better results in meeting the needs of the population. For this, primary data were collected and the data collection instrument was through a structured interview. The main challenges encountered are the people designated throughout the process, and especially when it involves the knowledge, skills and attitudes of managers. Therefore, there are a set of factors that are not fully meeting the needs of the sectors, due to the lack of effective management of methods and techniques